A quantitative analysis of model predictive control as energy management strategy for hybrid electric vehicles: A review. (November 2021) - Zhou, Quan; Du, Changqing
Abstract: This paper innovatively applies fuzzy comprehensive evaluation (FCE) method with analytic hierarchy process methodology (AHP) to quantitatively explore the academic value of literature about model predictive control (MPC) as energy management strategy (EMS) for hybrid electric vehicles (HEVs). Among that, Date of publication, Journal Impact Factor, Journal Cite Score and Times Cited are considered as evaluation factors of literature. Then classifications of MPC framework from six perspectives, such as hybrid types and working scenarios, prediction method, cost function, MPC solver and benchmark EMSs in the comparison, are proposed for the first time. The quantitative academic value of literature is reversely assigned to each perspective of MPC with the aid of above method and further study like benefits and limitations of each method. Finally, the academic contribution of method in each perspective is also obtained to objectively analyze future development trend of kinds of method in MPC framework. This paper can not only provide a new method to summarize and analyze the literature about works of interested area, but also supply a comprehensive and detailly view for relevant scholars with the effective suggestions. Highlights: Literature about MPC is quantitatively explored by fuzzy comprehensive evaluation. Classifications of MPC framework from six perspectives are discussed. Benefits and limitations of method applied in MPC are identified and analyzed. Analyzing future development trend through academic contribution is proposed.